The Relationship of Teacher's Perception to The Principal's Clinical Supervision and Teacher's Professional Competence With Work Ethics State Elementary School Teachers in The Sub-District Mustikajaya Bekasi City - Luviana, Eva; Baharuddin; Sugiarti, Diyah Yuli (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This study aims to determine 1) the relationship between teachers' perceptions of the principal's clinical supervision (X1) and the teacher's work ethic (Y), 2) the relationship between the teacher's professional competence (X2) and the teacher's work ethic (Y) 3) the relationship between teachers' perceptions of supervision principal clinical (X1) and teacher professional competence (X2) together with the teacher's work ethic (Y). The method used is quantitative-descriptive research. This research is correlational. The results of this study 1) there is a relationship between the teacher's perception of the principal's clinical supervision and the teacher's work ethic with a correlation coefficient of 8.2%, 2) there is a relationship between the teacher's professional competence and the teacher's work ethic with a correlation coefficient of 3.2%, 3) there is a relationship between the Teacher's Perception of the Principal's Clinical Supervision and the Teacher's Professional Competence together with the Teacher's Work Ethics with a correlation coefficient of 8.6%.